Genetic Testing in the Evaluation of Unexplained Cardiac Arrest: From the CASPER (Cardiac Arrest Survivors With Preserved Ejection Fraction Registry). (June 2017) - Mellor, Greg; Laksman, Zachary W.M.; Tadros, Rafik; Roberts, Jason D.; Gerull, Brenda; Simpson, Christopher S.; Klein, George J.; Champagne, Jean; Talajic, Mario; Gardner, Martin; Steinberg, Christian; Arbour, Laura; et al.
Abstract : Background—: Unexplained cardiac arrest may be because of an inherited arrhythmia syndrome. The role of genetic testing in cardiac arrest survivors without a definite clinical phenotype is unclear. Methods and Results—: The CASPER (Cardiac Arrest Survivors with Preserved Ejection Fraction Registry) is a large registry of cardiac arrest survivors where initial assessment reveals normal coronary arteries, left ventricular function, and resting ECG. Of 375 cardiac arrest survivors in CASPER from 2006 to 2015, 174 underwent genetic testing. Patients were classified as phenotype-positive (n=72) or phenotype-negative (n=102). Genetic testing was performed at treating physicians' discretion in line with contemporary guidelines and availability. All genetic variants identified from original laboratory reports were reassessed by the investigators in line with modern criteria. Pathogenic variants were identified in 29 (17%) patients (60% channelopathy-associated and 40% cardiomyopathy-associated genes) and 70 variants of unknown significance were identified in 32 (18%) patients. Prior syncope (odds ratio, 4.0; 95% confidence interval, 1.6–9.7) and a family history of sudden death (odds ratio, 3.2; 95% confidence interval, 1.1–9.4) were independently associated with the presence of a pathogenic variant. In phenotype-negative patients, broad multiphenotype genetic testing led to higher yields (21% versus 8%; P =0.04) but was associated with more variants of unknown significance (55% versus 5%; P <0.01). Conclusions—: Genetic testing identifies a pathogenic variant in a significant proportion of unexplained cardiac arrest survivors. Prior syncope and family history of sudden death are predictors of a positive genetic test. Both arrhythmia and cardiomyopathy genes are implicated. Broad, multiphenotype testing revealed the highest frequency of pathogenic variants in phenotype-negative patients. Clinical Trial Registration—: https://www.clinicaltrials.gov . Unique Identifier: NCT00292032 Abstract : Supplemental Digital Content is available in the text.